CLINICAL NURSES’ MORAL COURAGE IN TENURE OF NURSES: AN ANALITYC SURVEY - indah restika; Suarnianti; Yusran Haskas; Andi Sulfikar (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2023)
Background: The complexity of services that nurses must provide nowadays encourages nurses to develop their moral courage. A review of the literature reveals that no studies have been conducted to evaluate the association between clinical nurse tenure and their level of moral courage. Objectives: this study is to assess correlation between the tenure of nurses and the level of moral courage. Methods: analytic survey research at 5 hospitals in Makassar, including private and government hospitals with a total sample of 405 nurses. The sampling technique used multistage random sampling. The variables measured were tenure of nurses and the level of moral courage of nurses. The Professional Moral Courage Questionnaire is used for the variable moral courage (Cronbach 'alpha: 0.756). Data analysis using Mann Whitney test. Results: The majority of nurses with long and new tenure had moderate moral courage (new tenure 79 nurses; length tenure 238 nurses), and there was no significant difference in the moral courage level of nurses with long and new tenure (p=0.294). Conclusion: Considering the findings that nurse tenure has no effect on moral courage, nursing managers can consistently boost nurses' moral courage through external stimuli. A nurse who cannot face various ethical dilemmas in providing daily nursing care can result in moral distress.